2016
DOI: 10.1016/j.landurbplan.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the impact of urban development pathways on the local climate: A scenario-based analysis in the greater Dublin region, Ireland

Abstract: h i g h l i g h t s• The impact of different future development pathways on local climate are simulated.• Sprawling scenarios increased sensible/stored heat across 7.7-14.9% of the domain.• Greening rooftops resulted in the lowering the impact on local scale climate. a r t i c l e i n f o b s t r a c tIn this study, the impact of different urban development scenarios on neighbourhood climate are examined. The investigation considers the relative impact differing policy/planning choices will have on the local-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 64 publications
(52 reference statements)
0
23
0
1
Order By: Relevance
“…Chen concluded that both the spatial configuration of tree canopies and the vertical structure of tree canopies are important predictors for reducing land surface temperature (LST) during daytime and nighttime [13]. Also, specific urban structures and morphologies produce distinct microclimates [14][15][16][17][18], which means that in order to achieve effective urban heat island mitigation, it is necessary to understand and apply urban climatic information in urban planning. However, investigating the impacts of urban physical characteristics on microclimate is a difficult task because of the complexity and variety of land cover, surface structures, construction materials and human activities [19].…”
Section: Introductionmentioning
confidence: 99%
“…Chen concluded that both the spatial configuration of tree canopies and the vertical structure of tree canopies are important predictors for reducing land surface temperature (LST) during daytime and nighttime [13]. Also, specific urban structures and morphologies produce distinct microclimates [14][15][16][17][18], which means that in order to achieve effective urban heat island mitigation, it is necessary to understand and apply urban climatic information in urban planning. However, investigating the impacts of urban physical characteristics on microclimate is a difficult task because of the complexity and variety of land cover, surface structures, construction materials and human activities [19].…”
Section: Introductionmentioning
confidence: 99%
“…At the 10th International Conference on Urban Climate in 2018, it became clear that LCZ maps are now regarded as a global reference for urban land cover descriptions [10]. Since LCZ maps are intended for and already used in a range of different applications, such as climate models at various scales [11][12][13][14][15][16][17][18][19][20], land use change investigations [6], or the characterization of several hundreds of crowd-sourced citizen-weather stations in terms of their local-scale surroundings [21], there is a clear need for highly accurate classification results [22]. However, it is unclear what determines the final quality of a LCZ map derived with the WUDAPT level-0 methodology.…”
Section: Introductionmentioning
confidence: 99%
“…A climate-based classification of the city was developed as a method for urban heat island investigation [37,38]. Recent studies have combined the LCZs partition method, and a certain number of climate correlation analyses and scenario simulation prediction analyses have been carried out at the city macro level [39]. On the urban microscale level, research has focused on the effects influenced by building layouts and spatial structures.…”
Section: Academic Groupingsmentioning
confidence: 99%